Floating Prayer - Montrose, Victoria Rose (Journal of Religion in Japan, 2014)
With over forty thousand attendees every year, the Shinnyo-en Hawaii Lantern Floating—an adapted version of the traditional Japanese Buddhist obon ritual, tōrō nagashi—is among the largest annually held Buddhist rituals undertaken outside of Asia. One way to approach understanding of this rite is as an example of a ‘glocal’ Buddhist ritual. Drawing from Roland Robertson’s framework of glocalization, this study examines the steps Shinnyo-en took to adapt its global message to a new local culture. While other examples of the tōrō nagashi are found in Hawaii, none have developed on the rite to the extent that Shinnyo-en has. Some innovations include: moving the date of the rite to Memorial Day, the inclusion of local cultural elements and other religious groups, and allowing the public to personalize the individual lanterns. Through examples of the ritual’s various Hawaiian and global elements, I explain why the Shinnyo-en version of the lantern floating rite, over other versions of the same rite, came to reach its status as the Hawaiian Lantern Floating Ceremony. Finally this study argues for the important, often overlooked role of both ritual and new religious movements in globalization.